1978
DOI: 10.4141/cjas78-035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low Erucic Acid Rapeseed Oil Fed to Monkeys: Cardiac Lipids, Histochemistry and Pathology

Abstract: Male and female cynomolgus monkeys (Macaca fascicularis), equally divided as to sex, were fed, up to 24 wk, diets which contained 20% by weight of either soybean oil or Brassica napus cv. Tower rapeseed oil which contained 0.2% erucic acid. Long-chain monoenes appeared to accumulate in the cardiac lipids of both sexes fed Tower rapeseed oil. Histochemical studies suggested no myocardial damage associated with the feeding of either diet. Histopathological examination of the hearts of monkeys fed the two diets s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…It should be noted, however, that other strains of rat, namely Chester Beatty (17,20) and Wistar (18), showed only a low incidence and/or severity of heart lesions which was not increased with the intake of LEAR oils. Similar results were observed with mice (18), pigs (21)(22)(23)(24)(25), monkeys (26,27), ducks (28), and chicken (29) fed LEAR oils.…”
Section: Discussionsupporting
confidence: 79%
“…It should be noted, however, that other strains of rat, namely Chester Beatty (17,20) and Wistar (18), showed only a low incidence and/or severity of heart lesions which was not increased with the intake of LEAR oils. Similar results were observed with mice (18), pigs (21)(22)(23)(24)(25), monkeys (26,27), ducks (28), and chicken (29) fed LEAR oils.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, at 16 weeks the cardiac lipids of chickens fed Regular RSO contain considerably more of 20:1 and more 22:1 than those of the rat or pig. Similar to the pig (Friend et al, 1976;Ah erne et al, 1976) and monkey (Kramer et al, 1978), the chickens fed low 22:1 RSO's (Tower and Candle) in this study did not develop myocardial lesions as did the rats fed (Kramer et al, 1979), chickens (current study), pigs (Von U. Peterson et al, 1979), and monkeys (Beare-Rogers and Nera, 1972) fed diets containing rapeseed oil high in eicosenoic (12 to 14%) and erucic (25 to 30%) acids for different durations of time.…”
Section: C Q Cmentioning
confidence: 67%
“…The male rat is different from the pig and monkey with respect to the occurrence of myocardial lesions when high levels of these oils are fed (Kramer et al, 1978). Vogtmann et al (1973) demonstrated a decrease in body weight of chickens fed diets containing high levels of RSO high in 22:1, whereas the reverse was true with lard.…”
Section: Introductionmentioning
confidence: 89%